Pathologic Findings Suggest Long-term Abnormality after Conservative Management of Complex Acute Appendicitis. Issue 3 (March 2015) - Rosen, Matthew; Chalupka, Andrew; Butler, Kathryn; Gupta, Alok; Odom, Stephen R.
Perforated or phlegmonous appendicitis is often treated with antibiotics and drainage as needed. The rationale, risk of recurrence, timing, or even the necessity of subsequent elective interval appendectomy (IA) is debated. We retrospectively reviewed all appendectomies performed at Beth Israel Deaconess Medical Center between 1997 and 2011. We determined if the appendix was removed emergently or as IA. Demographic characteristics, hospital length of stay, computed tomography (CT) results, and operation type (open or laparoscopic) were determined. In IA specimens, narrative pathology reports were assessed for evidence of anatomic, acute, or chronic abnormality. A total of 3562 patients had their appendix removed during this time period. Thirty-four patients were identified as having IA. Of these, only three (8.8%) had a pathologically normal appendix. All three patients were female and all had initially abnormal CTscans. Eight specimens (23.5%) had evidence of chronic and 10 (29.4%) had evidence of acute appendicitis. An additional 10 (29.4%) specimens contained a combination of acute and chronic inflammation. Mean time to operation in the IA group was 57.1 days (range, nine to 234 days) after index diagnosis by CTscan. Given the high percentage of IA specimens with acute or chronic appendicitis and the extremely high proportion (91%) of patients with pathologically abnormal specimens, it appears that IA may be justified in most cases.